Peningkatan Daya Saing UMKM Tauge Desa Cibatu Melalui Pelatihan Branding dan Pemasaran Digital Berbasis Syariah - Jalaludin Jalaludin; Hasan Tiar Harahap; Syifa Sopiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) – Sekolah Tinggi Agama Islam (STAI) Pelita Nusa Bandung Barat, 2024)
Based on the results of observations, the PKM team found several unique phenomena related to Bean Sprouts MSMEs in Cibatu Village, one of which is that Bean Sprouts MSME players are still taboo about digital marketing, so the marketing carried out at this time is limited to relying on people who know and come to the business location. The second phenomenon is that business location access is far from highway access and does not have a name sign. The third phenomenon is that the business location has not been registered on google maps, so new visitors have difficulty coming directly to the business location. The purpose of this PKM is to conduct training in branding and sharia-based digital marketing for Bean Sprouts MSME players in Cibatu Village. The methods used in this PKM are going to the field to make observations, providing solutions to problems, implementing the solutions offered, monitoring and evaluating Bean Sprouts MSMEs in Cibatu Village. Community service on Increasing the Competitiveness of Bean Sprouts MSMEs in Cibatu Village Through Sharia-Based Digital Branding and Marketing Training Allhamdulillah already knows the importance of brand image and sharia-based digital marketing. In addition, the name sign that the PKM team provided seemed to have a positive impact, marked by the fact that many people began to recognize the production or manufacture of bean sprouts in Cibatu Village. The addition of locations on Google Maps also has a positive impact in the form of making it easier for new customers to visit the location of the Cibatu Village Bean Sprouts UMKM Purwakarta. Then the NIB that has been owned is proof that UMKM Tauge is a responsible business.